Evaluasi Pemanfaatan Koleksi Anak di Dinas Perpustakaan dan Kearsipan Kabupaten Pidie - Cut Putroe Yuliana; Nuzul Rahmah; T.Ade Vidyan Maqfirah (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Collection evaluation completes the cycle of a collection development process in a library. This activity generates data including how useful it is to provide collections for certain groups such as children. There is no debate that many benefits of reading books for children include developing language skills and creative thinking. Therefore, the availability of access to collections and suitability for children's needs are important to consider in collection management. This paper evaluates the use of the children's collection held at the Pidie District Public Library. The aim is to assess the use of children’s collections by elementary school students who visited the public library in Pidie district. Fiction collection circulations were analysed based on its genre. The method used is descriptive with a qualitative approach. Data obtained through circulation statistic, interview and observation.The result of research based on usage statistics from November 2021 to Oktober 2022 showed that total usage of children collections were 672 books per year and fiction usage collection for 456 times. The most frequent- used of fiction collection was fairytale, followed by the storybooks, short stories, poetry, novels and folklore. Students can borrow only 2 to 3 title of the books within a week. Students really appreciate the availability of children's collections in public libraries due to the limitation of their school libraries’ collections. Nevertheless, students suggest that public library should develop the variety of fiction collections. Holdings of fiction collections only 193 titles or 470 copies from total holdings 247 titles or 730 copies of children collections. Therefore, this result can assist the Pidie Regent Public Library to manage children collection development decisions in future